Early Marriage and Divorce in Indonesia: A Systematic Literature Review of Socioeconomic, Educational, and Health Dimensions - Riska; M.Arif Mustofa; Zeni Sunarti (Zabags International Journal of Islamic Studies, 2025)
This article examines the complex relationship between early marriage and divorce in Indonesia, a phenomenon that continues to generate significant social, cultural, and economic implications. The study aims to identify the structural and individual factors driving early marriage and its role in increasing vulnerability to divorce, as well as to highlight the broader impacts on education, reproductive health, and social welfare. Employing a systematic literature review approach, the analysis was conducted through a comprehensive search of open-access academic journals, using inclusion and exclusion criteria to ensure the credibility and relevance of selected studies. The findings reveal that early marriage often correlates with limited educational attainment, gender inequality, financial instability, and insufficient reproductive health knowledge, all of which contribute to higher divorce rates. Furthermore, the review shows that cultural norms, legal inconsistencies, and the lack of effective policy implementation exacerbate the sustainability challenges of early-age marriages. This study contributes theoretically by deepening the discourse on early marriage and divorce as interconnected issues within family sociology and public health, while practically providing insights for policymakers to design preventive and empowerment-based interventions.